Gonadotropin-Inhibitory Hormone Plays Roles in Stress-Induced Reproductive Dysfunction - Iwasa, Takeshi; Matsuzaki, Toshiya; Yano, Kiyohito; Irahara, Minoru (Frontiers in Endocrinology, 2017)
Physical and psychological stressors suppress hypothalamic-pituitary-gonadal (HPG) axis activity and sexual behavior and consequently induce reproductive dysfunction. Recently, it has been shown that gonadotropin-inhibitory hormone (GnIH), also called RFamide-related peptide 3 (RFRP) in mammals, which is a potent inhibitory regulator of GnRH and gonadotropin, is involved in stress-induced reproductive dysfunction. GnIH/Rfrp (the gene coding RFRP-3) expression and activity are increased by psychological and immune stress, and this alteration suppresses GnRH and gonadotropin secretion. Glucocorticoid acts as a mediator that interacts between stress and hypothalamic GnIH/RFRP-3. GnIH/RFRP-3 also plays important roles in stress-induced suppression of sexual behavior and infertility, and genetic silencing of GnIH/Rfrp completely recovers sexual behavior and fertility. This review summarizes what is currently known about the roles of GnIH in stress-induced reproductive dysfunction.